Book Review: F. Baylis & A. Ballantyne (2016) Clinical Research Involving Pregnant Women - Wada, Kyoko (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2019)
There is a paucity of scientific evidence to support prenatal care due to the wide exclusion of pregnant women from clinical research. Baylis and Ballantyne’s book, Clinical Research Involving Pregnant Women, stands as a powerful advocate for promoting clinical research with pregnant women, although a few issues may deserve further attention to facilitate such research.